2018
DOI: 10.1021/jacs.8b02283
|View full text |Cite
|
Sign up to set email alerts
|

Novobiocin Enhances Polymyxin Activity by Stimulating Lipopolysaccharide Transport

Abstract: Gram-negative bacteria are challenging to kill with antibiotics due to their impenetrable outer membrane containing lipopolysaccharide (LPS). The polymyxins, including colistin, are the drugs of last resort for treating Gram-negative infections. These drugs bind LPS and disrupt the outer membrane; however, their toxicity limits their usefulness. Polymyxin has been shown to synergize with many antibiotics including novobiocin, which inhibits DNA gyrase, by facilitating transport of these antibiotics across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 49 publications
1
51
1
Order By: Relevance
“…Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram‐positive bacteria, and between the peptidoglycan and the outer membrane of the Gram‐negative bacteria . Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram‐positive bacteria and with respect to lipopolysaccharide transport in Gram‐negative bacteria . Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope‐targeting Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram‐positive bacteria, and between the peptidoglycan and the outer membrane of the Gram‐negative bacteria . Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram‐positive bacteria and with respect to lipopolysaccharide transport in Gram‐negative bacteria . Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope‐targeting Antibioticsmentioning
confidence: 99%
“…77,78 Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram-positive bacteria 69,[79][80][81][82][83][84] and with respect to lipopolysaccharide transport in Gram-negative bacteria. [85][86][87][88][89][90] Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope-targeting Antibioticsmentioning
confidence: 99%
“…After synthesized the analogs ( Figure 3B), we examined their activities against E. coli ( Figure 3C). Although the replacement of succinate by cyclohexane-1,2-dicarboxylic acid produces a prodrug (6) with rather low activity (MIC > 200 M), the conjugation of GG to 6 significantly increases the activity of the prodrug (7, MIC = 50 M). Because the ciprofloxacin derivative, with the diglycine conjugated at the carboxylic acid of ciprofloxacin, hardly shows activity against E. coli (Scheme S5 and Figure S7), we made a ciprofloxacin derivative (8), which has 2-hydroxyacetic acid attach to the piperazine end of ciprofloxacin, for conjugating GG to ciprofloxacin.…”
Section: Scheme 1 Illustration Of Diglycine Speeding Up the Regeneramentioning
confidence: 99%
“…4 Thus, there is an urgent need for developing new antimicrobial approaches against MDR bacterial pathogens. Besides investigating novel agents against new targets in bacteria [6][7][8][9] via previously unexplored mechanisms, another strategy is to enhance the efficacy and safety of the existing antibiotics via drug combinations or increasing specificity. For example, Kahne et al demonstrated that the use of novobiocin analogs greatly lower the dose of polymyxins against Gram-negative bacteria via inhibiting DNA gyrase, binding LptB, and disrupting outer membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation